Empowering Posyandu through Stunting Prevention Training and Education - Dwi Ariyani; Reza Anindita; Resti Nur Arini; Maulin Inggraini (International Journal of Community Service Learning, 2025)
Stunting remains a significant health problem in Indonesia, especially for toddlers in areas with limited access to good nutrition and health services. The purpose of the Community Service Program (PKM) is to improve understanding of clean water management and the provision of nutritious food for pregnant women and toddlers, as well as to empower Posyandu groups. The methods used include the preparation, implementation, and evaluation stages, with a focus on education and training. The subjects in this study were mothers, babies, toddlers, and pregnant women. The data analysis of this study used descriptive data analysis. Data collection used interviews and documentation. The results of this study indicate that empowering Posyandu through training and education on stunting prevention has a positive impact on increasing the knowledge and skills of Posyandu cadres. Before the training, most cadres had a limited understanding of the concept of stunting, causative factors, and prevention efforts. However, after being given intensive training, there was a significant increase in cadres' understanding of the importance of good parenting, providing balanced nutritious food, and routine child growth monitoring practices. This study concludes that providing stunting prevention education can increase the knowledge and awareness of pregnant women and mothers with babies and toddlers regarding efforts to prevent stunting through providing balanced nutrition and clean water sanitation. The implications of this study indicate that empowering Posyandu through training and education on stunting prevention can be an effective strategy for improving the quality of public health services.